2023
DOI: 10.1111/jvh.13792
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical efficacy of pegylated interferon treatment in patients with different phases of chronic HBV infection: A real‐world analysis

Abstract: Although there are therapeutic advantages for hepatitis B virus (HBV) withpegylated interferon alpha (peg‐IFNα) treatment compared with nucleos(t)ide analog (NAs) therapy, the effect difference in infected population at different phases has not been well established. We studied the clinical efficacy of peg‐IFNα in two populations with HBV infection, including inactive HBsAg carrier (IHC) and chronic hepatitis B (CHB). A total of 328 HBV‐infected patients were included in this real‐world analysis. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…A recently published European study showed that 24-week HBsAg decline during PegIFNα-based treatment was superior to 12-week HBsAg decline for predicting subsequent HBsAg loss [23], which was confirmed in the present study. In addition, this study confirmed the conclusion that the lower the baseline HBsAg level, the higher the functional cure rate, as reported previously [12,13,24–27].…”
Section: Discussionsupporting
confidence: 92%
“…A recently published European study showed that 24-week HBsAg decline during PegIFNα-based treatment was superior to 12-week HBsAg decline for predicting subsequent HBsAg loss [23], which was confirmed in the present study. In addition, this study confirmed the conclusion that the lower the baseline HBsAg level, the higher the functional cure rate, as reported previously [12,13,24–27].…”
Section: Discussionsupporting
confidence: 92%
“…Emerging data suggest that baseline characteristics and the extent of early on-treatment HBsAg reduction may predict the possibility of HBsAg loss with Peg-IFN treatment ( Moucari et al., 2009 ; Rijckborst et al., 2010 ; Yeo et al., 2019 ). We found that baseline HBsAg level and HBsAg decline rates from baseline to 12 weeks and 24 weeks were all useful independent predictors of HBsAg clearance, which have been supported by many previous studies in individualized on-treatment decision-making ( Hu et al., 2018 ; Zheng et al., 2019 ; Zhang et al., 2023 ). In our study, the decline of HBsAg from baseline to 12 weeks and 24 weeks of more than 80% and 98% is a strong predictor of HBsAg clearance.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, Zhang et al. ( Zhang et al., 2023 ) conducted a study about the comparison of Peg-IFN in NA-experienced patients and IHCs. They showed that the rates of HBsAg loss were 36.8% and 32.6% in the IHC group and NA add-on Peg-IFN group, respectively, after 24-week treatment, but their research lacked Peg-IFN-free control groups.…”
Section: Discussionmentioning
confidence: 99%